(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this investigation, Silver telluride (Ag2Te) thin films have been successfully deposited onto FTO glass substrate using electro deposition method to investigate the influence of Ce doping on optical properties of Ag2Te films. Silver trioxonitrate (V) and tellurium (iv) oxide were the precursors used for silver and tellurium ions. Depositions of films made from cerium-doped silver telluride were conducted at room temperature. The percentages concentration of cerium dopant used in this investigation are 2.5%, 5.0%, 7.5% and10.0%. The optical properties of the thin films were characterized using Uv-Vis spectrometry. Absorbance results confirm that increasing Ce concentration significantly increases the absorbance of Ag2T films across the UV, VIS, and NIR regions. The 10.0% Ce-doped sample demonstrates the highest absorbance across all regions, with values of 43.36% at 365 nm, 42.68% at 400 nm, 34.00% at 700 nm, and 35.16% at 1100 nm, indicating the strong influence of cerium in enhancing light absorption. This trend reflects that as Ce concentration increases, absorbance improves significantly in all spectral regions, suggesting that Ce doping introduces additional localized states that facilitate electronic transitions, thereby enhancing the films' optical properties. The transmittance of Ag2Te and Ce-doped Ag2Te films decreases notably with increasing cerium concentration across the UV, VIS, and NIR regions. This decline in transmittance with increasing Ce concentration is consistent with the corresponding increase in absorbance suggesting that Ce doping enhances light absorption, thus reducing the amount of light transmitted through the films. Cerium doping enhances reflectance slightly, particularly in the NIR regions, likely due to increased surface roughness and scattering effects introduced by Ce incorporation. The extinction coefficient (k) of silver telluride and cerium-doped silver telluride films generally increases with wavelength, indicating higher optical absorption at longer wavelengths. Other optical results were also presented.